Effects of uniaxial stress on dielectric properties of ferroelectric ceramics - Rattikorn Yimnirun (2018)
The effects of uniaxial stress on the dielectric properties of ceramics in PMN-PZT system are investigated. Ceramics with the formula (x)Pb(Mg1/3Nb2/3)O3-(1 - x)Pb(Zr0.52Ti0.48)O3when x = 0.0, 0.1, 0.3, 0.5, 0.7, 0.9 and 1.0 are prepared by a conventional mixed-oxides method. The sintered ceramics are perovskite materials with their physical properties proportionally depending on the PMN and PZT contents. The dielectric properties under the uniaxial stress of the unpoled and poled PMN-PZT ceramics are observed at stress levels up to 5 MPa. For the unpoled ceramics, the dielectric properties do not change significantly with the applied stress and the changes are independent of the ceramic compositions. For the poled ceramics, on the other hand, the dielectric constant of the PZT-rich compositions increases slightly, while that of the PMN-rich compositions decreases with increasing applied stress. In addition, changes in the dielectric loss tangent with stress are found to be composition independent. This study clearly shows the influences of the domain re-orientation, domain wall motion, degradation and depoling mechanisms on the variation of the dielectric properties of PMN-PZT ceramics under the uniaxial stress. © 2005 Elsevier B.V. All rights reserved.